2019
DOI: 10.1001/jamasurg.2018.4282
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Uncomplicated Appendicitis Among Privately Insured Patients

Abstract: professionals have shown significant interest in nonoperative management for uncomplicated appendicitis, but long-term population-level data are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 44 publications
3
47
2
Order By: Relevance
“…Yet, surgery and perioperative care of children with appendicitis can be both challenging and expensive, and avoiding complications is of the highest priority. 5,[18][19][20] In line with earlier studies, 14,21 our data report a very low mortality and a low overall risk of complications, and we conclude that treatment in general was safe and effective in several aspects. However, since appendicitis is relatively common during childhood and adolescence, even low rates of complications lead to significant disease burden and costs beyond the index hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, surgery and perioperative care of children with appendicitis can be both challenging and expensive, and avoiding complications is of the highest priority. 5,[18][19][20] In line with earlier studies, 14,21 our data report a very low mortality and a low overall risk of complications, and we conclude that treatment in general was safe and effective in several aspects. However, since appendicitis is relatively common during childhood and adolescence, even low rates of complications lead to significant disease burden and costs beyond the index hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of appendiceal cancers, however, are not diagnosed preoperatively and present as acute appendicitis, which makes our patient cohort relevant to addressing our clinical question . Finally, the overall incidence of nonoperative management of acute appendicitis has been historically low – a study of privately insured patients in the country reported only 4.5% of patients with acute appendicitis being treated without surgery . However, there has been increasing public awareness on the treatment options for appendicitis; a survey in 2016 showed up to 9.4% of individuals would opt for nonoperative management of their acute appendicitis when presented with treatment options, and in the pediatric population, nonoperative management increased by 20.4% between the years of 2010‐2016 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Finally, the overall incidence of nonoperative management of acute appendicitis has been historically lowa study of privately insured patients in the country reported only 4.5% of patients with acute appendicitis being treated without surgery. 32 However, there has been increasing public awareness on the treatment options for appendicitis; a survey in 2016 showed up to 9.4% of individuals would opt for nonoperative management of their acute appendicitis when presented with treatment options, and in the pediatric population, nonoperative management increased by 20.4% between the years of 2010-2016. 33,34 Despite these limitations, our study has many strengths and provides contemporary, generalizable data, which can be used to help clinicians best educate and counsel patients in a time of changing treatment practices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ILA is preferred in most pediatric cases of appendicitis. However, some researchers disapprove of the use of ILA because of increased hospital costs, risk of recurrence, and strong in ammatory adhesion [13][14][15]. However, with the recent technical improvements in laparoscopic surgery, ELA has been reported to be equivalent to ILA in terms of the frequency of complications [16][17][18].…”
mentioning
confidence: 99%